Fixed Cutaneous Sporotrichosis Due to Sporothrix globosa - Liu, Fang (Clin Cosmet Investig Dermatol, 2021)
PURPOSE: This report describes a case of a skin sporotrichosis infection and the steps taken to identify an effective antifungal treatment. PATIENTS AND METHODS: A 50-year-old woman from Jilin province, China, presented complaining of a small mass that had been on her right upper eyelid for two years. A skin biopsy was taken and submitted for bacterial and mycological assessment. Bacterial culture from the lesion was negative, but a fungal culture was positive. In vitro susceptibility test was performed to assess its susceptibility to antifungal drugs. RESULTS: The skin biopsy showed infectious granuloma. Fungal culture was identified as Sporothrix globosa based on both the morphological features and confirmation by the molecular method; it was resistant to many kinds of antifungal drugs, including amphotericin B, voriconazole, fluconazole, and caspofungin. However, it was relatively sensitive to itraconazole. The patient was prescribed 0.2 g itraconazole to be taken twice per day. One month later, she had almost completely recovered from her symptoms. The treatment lasted for 3 months and her liver function and renal function were normal at the endpoint. CONCLUSION: Itraconazole was an effective treatment in this case of a multidrug-resistant sporotrichosis caused by S. globosa.